1H NMR reveals dynamic changes of primary metabolites in purple passion fruit (Passiflora edulis Sims) juice during maturation and ripening - Md Nor, Shahidah; Ding, Phebe; Abas, Faridah; Mediani, Ahmed (Multidisciplinary Digital Publishing Institute, 2022)
Passion fruit (Passiflora edulis Sims) is a tropical fruit that shows an increasing demand from global fresh fruit industries. The fruit is known to have climacteric properties that allow it to achieve ripening during distribution and transportation. However, the metabolic alterations that occur during ripening are poorly understood. Thus, this study was conducted to analyze the metabolites in passion fruit juice at different harvesting stages (35, 42, 49, 56 and 63 days after anthesis), employing 1H NMR spectroscopy combined with chemometric analysis. A total of 30 metabolites were successfully identified using 1H NMR, the majority of which belong to primary metabolites, consisting of 14 amino acids, 7 sugars and 6 organic acids. Nevertheless, only three secondary metabolites were detected. Analyzing the metabolites using multivariate analysis reveals 13 of the metabolites were highly influential metabolites. These primary metabolites play essential roles in the maturation and ripening of fruit. Glycolysis, the tricarboxylic acid (TCA) cycle and the shikimate pathway were differentially regulated during maturation and ripening of passion fruit. Profiling the metabolome of fruit during maturation and ripening reveals that all metabolites are interconnected with each other to cause maturation and ripening in passion fruit. This work will enhance the knowledge of physiological changes in purple passion fruit during maturation and ripening.